Pemberdayaan Lingkungan Masyarakat Melalui Sosialisasi Hidroponik System Wick (sumbu) Di Desa Tanjung Simandolak, Kecamatan Benai, Kabupaten Kuantan Singingi, Provinsi Riau - Syahputra Syahputra; Indra Suharman; Divo Afrianto; Enggar Akbar Nur Izza; Muhammad Sorim Arkan; Septia Nursa; Amirah Mardhiyah; Ayu Lestari; Mika Handayani; Eka Wahyu Ningsih; Retno Tri Pratiwi (FKIP, Universitas Palangka Raya, 2023)
The socialization of hydroponics to the village community is an effort to develop the independence and welfare of the community by improving knowledge, attitudes, skills, Hydroponics is a cultivati Wick hydroponics is a simple hydroponic method that uses a wick as a link between nutrients and the roots of the growing media. This activity was carried out in Tanjung Simandolak Village, Benai District, Kuantan Singingi, Riau. This activity began with a theoretical and practical explanation with pakcoy mustard plants as an example, the practice carried out starting from seed sowing, wick system, transplanting and continued with a discussion session. The results of this activity are that the Tanjung Simandolak village community knows hydroponics in general, wick system hydroponics, plant maintenance, handing over hydroponics to the This activity adds to the knowledge and insight of the Tanjung Simandolak village community about hydroponics and can spread and teach the knowledge.